A Common Factors Approach to Psychotherapy With Chronically Suicidal Patients: Wrestling With the Angel of Death. Issue 3 (3rd July 2017) - Yager, Joel; Feinstein, Robert E.
Abstract : Objective : Conducting psychotherapy with chronically suicidal patients challenges clinical decision making and emotional self-management in both trainees and seasoned practitioners. Educators and trainees have noted the need for additional teaching materials in these areas. This article is intended to address these needs. Methods : We review the literature on evidence-based, suicide-oriented psychotherapies; consider commonalities among them; and integrate these findings with observations and suggestions from older professional literature and anecdotal clinical wisdom. Results : Based on these sources, we describe a common factors–based approach for clinicians undertaking the ongoing psychotherapy of chronically suicidal patients, to be practiced within a comprehensive treatment framework that addresses safety planning as well as multimodal interventions including psychosocial and biological approaches. We discuss initial considerations; a checklist of motivations, coping styles, defenses, existential, spiritual, and religious issues, attachments and relationships to be explored in delineating directions to be undertaken in psychotherapy; technical issues for ongoing psychotherapy; perspectives that have been helpful for patients; and coping strategies for countertransference management. Conclusions : Patients are best served by clinicians who focus on the alliance, actively engage chronically suicidal patients and their families, directly confront warning signs, routinely address the many psychological issues mentioned, and carefully attend to their own countertransference reactions and capacities for emotional regulation. Using these strategies, techniques, and tactics, clinicians are better equipped to help chronically suicidal patients reduce suicide-related ideations, plans, and attempts, and, perhaps, completed suicides.